Correlation of Stress in Silicon Carbide Crystal and Frequency Shift in Micro-Raman Spectroscopy. Issue 1693 (13th June 2014) - Sugiyama, N.; Yamada, M.; Urakami, Y.; Kobayashi, M.; Masuda, T.; Nishikawa, K.; Hirose, F.; Onda, S.
ABSTRACT: The correlation of stress in Silicon Carbide (SiC) crystal and frequency shift in micro- Raman spectroscopy was determined by an experimental method. We applied uniaxial stress to 4H- and 6H-SiC single crystal square bar specimen shaped with (0001) and (11-20) faces by four point bending test, under measuring the frequency shift in micro-Raman spectroscopy. The results revealed that the linearity coefficients between stress and Raman shift were -1.96 cm -1 /GPa for FTO(2/4)E2 on 4H-SiC (0001) face, -2.08 cm -1 /GPa for FTO(2/4)E2 on 4H-SiC (11-20) face and -2.70 cm -1 /GPa for FTO(2/6)E2 on 6H-SiC (0001) face. Determination of these coefficients has made it possible to evaluate the residual stress in SiC crystal quantitatively by micro-Raman spectroscopy. We evaluated the residual stress in SiC substrate that was grown in our laboratory by utilizing the results obtained in this study. The result of estimation indicated that the SiC substrate with a diameter of 6 inch remained residual stress as low as ±15 MPa.